2016
DOI: 10.1073/pnas.1524229113
|View full text |Cite
|
Sign up to set email alerts
|

Junctophilin-4, a component of the endoplasmic reticulum–plasma membrane junctions, regulates Ca 2+ dynamics in T cells

Abstract: Orai1 and stromal interaction molecule 1 (STIM1) mediate store-operated Ca 2+ entry (SOCE) in immune cells. STIM1, an endoplasmic reticulum (ER) Ca 2+ sensor, detects store depletion and interacts with plasma membrane (PM)-resident Orai1 channels at the ER-PM junctions. However, the molecular composition of these junctions in T cells remains poorly understood. Here, we show that junctophilin-4 (JP4), a member of junctional proteins in excitable cells, is expressed in T cells and localized at the ER-PM junction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 42 publications
0
66
0
Order By: Relevance
“…In a recent study by Woo et al (2016), it was shown that overexpression of JPH4 is involved in the recruitment of stromal interaction molecule 1 (STIM1) to the plasma-membrane-ER junctions in T cells, where JPH4 is also implicated in regulating Ca 2+ homeostasis (Woo et al, 2016). Our distance-based colocalisation analysis indicates that the increased cardiac JPH2 is largely associated with RyR clusters in junctions, which is also consistent with the observation of extended co-clusters of JPH2 and RyRs (Fig.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In a recent study by Woo et al (2016), it was shown that overexpression of JPH4 is involved in the recruitment of stromal interaction molecule 1 (STIM1) to the plasma-membrane-ER junctions in T cells, where JPH4 is also implicated in regulating Ca 2+ homeostasis (Woo et al, 2016). Our distance-based colocalisation analysis indicates that the increased cardiac JPH2 is largely associated with RyR clusters in junctions, which is also consistent with the observation of extended co-clusters of JPH2 and RyRs (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Although the effect of altered JPH2 expression on the t-system has been documented in some detail, the effect of JPH2 expression on RyR organisation has not been investigated directly. Junctophilin-4 (JPH4) has been identified as a key component in the plasma-membrane-endoplasmic reticulum (PM-ER) junctions in T cells, where it is involved in recruitment of Ca 2+ -sensing proteins to these domains (Woo et al, 2016), indicating that the JPH family plays a role in junctional protein organisation. A difficulty in revealing RyR cluster properties stems from the limited resolution of conventional fluorescence imaging which cannot resolve cluster structures.…”
Section: Introductionmentioning
confidence: 99%
“…protein anchors and of these, the junctophilin family is perhaps one of the best understood (Takeshima et al, 2015). Moreover, deletion or downregulation of JPH1 and JPH2 has been shown to impair SOCE in muscle cells (Hirata et al, 2006;Li et al, 2010), while downregulation of JPH4 impaired SOCE in Tcells (Woo et al, 2016). Yet, to the best of our knowledge the expression profile and potential function of juctophilins in sensory neurons is hitherto unreported.…”
Section: Expression Of Junctophilins In Sensory Neurons Er-pm Junctimentioning
confidence: 99%
“…Stromal Interaction Molecule (STIM) and Orai are the key molecular components of SOCE, but in addition other proteins like CRACR2A (CRAC regulator 2A; Srikanth et al, 2010) and Junctophilin-4 (Woo et al, 2016) modulate the strength and duration of the Ca 2+ signal and subsequent downstream events. While CRACR2A facilitates STIM/Orai coupling after ER store-depletion (Srikanth et al, 2010), Junctate and Junctophilin help define ER-PM junctions suitable for STIM/Orai coupling (Srikanth et al, 2012; Woo et al, 2016).…”
Section: Septins Regulate Socementioning
confidence: 99%
“…While CRACR2A facilitates STIM/Orai coupling after ER store-depletion (Srikanth et al, 2010), Junctate and Junctophilin help define ER-PM junctions suitable for STIM/Orai coupling (Srikanth et al, 2012; Woo et al, 2016). A genome wide screen in HeLa cells identified Septins as positive regulators of SOCE (Sharma et al, 2013).…”
Section: Septins Regulate Socementioning
confidence: 99%